The Relationship Between Family and Peer Support and Stress Levels of Final-Year Students in Thesis Writing - Sholehah, Annisa; Fitri, Nurwijaya; Mardiana, Nova (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to determine the relationship between family and peer support and the stress level of final year students in the preparation of thesis. It is hoped that the higher the support received, the lower the level of stress experienced. This study used a quantitative method with a correlational design and a cross sectional approach, involving 55 samples taken by simple randomization. Data collection was carried out through questionnaires, and data analysis using the Spearman Rank test with a significance level of α = 0.05. The results showed that family support had a value of ρ = 0.003 with r = -0.397, which indicates a negative relationship. Meanwhile, peer support had a value of ρ = 0.001 with r = -0.420, also indicating a negative relationship. This shows that there is a significant relationship between family and peer support and student stress levels. The higher the support received, the lower the level of stress students experience, and vice versa. The implication of this study is the importance of forming support groups between students as well as open communication with family, friends, academic supervisors, and thesis supervisors in overcoming difficulties during the thesis preparation process.